Pesticide Residues in Canned Foods, Fruits, and Vegetables: The Application of Supercritical Fluid Extraction and Chromatographic Techniques in the Analysis - Mohamed H. EL-Saeid (The Scientific World Journal)
Multiple pesticide residues have been observed in some samples of canned foods, frozen vegetables, and fruit jam, which put the health of the consumers at risk of adverse effects. It is quite apparent that such a state of affairs calls for the need of more accurate, cost-effective, and rapid analytical techniques capable of detecting the minimum concentrations of the multiple pesticide residues. The aims of this paper were first, to determine the effectiveness of the use of Supercritical Fluid Extraction (SFE) and Supercritical Fluid Chromatography (SFC) techniques in the analysis of the levels of pesticide residues in canned foods, vegetables, and fruits; and second, to contribute to the promotion of consumer safety by excluding pesticide residue contamination from markets. Fifteen different types of imported canned and frozen fruits and vegetables samples obtained from the Houston local food markets were investigated. The major types of pesticides tested were pyrethroids, herbicides, fungicides, and carbamates.By using these techniques, the overall data showed 60.82% of the food samples had no detection of any pesticide residues under this investigation. On the other hand, 39.15% different food samples were contaminated by four different pyrethroid residues ± RSD% ranging from 0.03 ± 0.005 to 0.05 ± 0.03 ppm, of which most of the pyrethroid residues were detected in frozen vegetables and strawberry jam. Herbicide residues in test samples ranged from 0.03 ± 0.005 to 0.8 ± 0.01 ppm. Five different fungicides, ranging from 0.05 ± 0.02 to 0.8 ±0.1 ppm, were found in five different frozen vegetable samples. Carbamate residues were not detected in 60% of investigated food samples. It was concluded that SFE and SFC techniques were accurate, reliable, less time consuming, and cost effective in the analysis of imported canned foods, fruits, and vegetables and are recommended for the monitoring of pesticide contaminations.